Analisis Pemahaman Mahasiswa Muslim Tentang Riba - mubaraq, abd; Rusandry, Rusandry; Atiqah, Nur (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to analyze the understanding of Muslim students about riba. The research uses descriptive qualitative research methods carried out through descriptive descriptions of words, or sentences, which are arranged carefully and systematically from collecting data to interpreting and going down to the field and interviewing respondents directly, the research used is the frequency distribution method (percentage). The sample in this study used 50 samples who were interviewed using descriptive methods and frequency distribution methods. The results showed that: the understanding of Muslim students on the definition of riba students still do not understand due to the lack of in-depth discussion and the ability of students' understanding of the definition of riba itself, regarding the difference between riba fadhl and riba nasi'ah found that students already understand the difference between riba fadhl and riba nasi'ah besides the understanding of Muslim students on six ribawi goods found the results students do not understand, and student understanding of usury jahiliyah found that Muslim students already understand.